Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/ndt/gfr257
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase (MTHFR) polymorphism A1298C (Glu429Ala) predicts decline in renal function over time in the African-American Study of Kidney Disease and Hypertension (AASK) Trial and Veterans Affairs Hypertension Cohort (VAHC)

Abstract: We conclude that the MTHFR-coding polymorphism at A1298C is associated with renal decline in African-Americans with hypertensive nephrosclerosis and is supported by a veteran cohort with a primary care diagnosis of hypertension. Further investigation is needed to confirm such findings and to determine what molecular mechanism may contribute to this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 65 publications
0
16
0
1
Order By: Relevance
“…with high genetic complexity, as indicated by multiple independent associations with BP and renal phenotypes in the human population (Kato et al 2000;Jiang et al 2004;Zhang et al 2005;Levy et al 2009;Newton-Cheh et al 2009a,b;Chen et al 2010;Tomaszewski et al 2010;Johnson et al 2011;Liu et al 2011;Fung et al 2012). By combining rat phenotype data ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…with high genetic complexity, as indicated by multiple independent associations with BP and renal phenotypes in the human population (Kato et al 2000;Jiang et al 2004;Zhang et al 2005;Levy et al 2009;Newton-Cheh et al 2009a,b;Chen et al 2010;Tomaszewski et al 2010;Johnson et al 2011;Liu et al 2011;Fung et al 2012). By combining rat phenotype data ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Strains were tested for eight cardiovascular disease (CVD)-associated phenotypes following a 10-d high-salt challenge (see Methods and Table 1). Because BP and renal phenotypes are most commonly reported in human studies (Kato et al 2000;Jiang et al 2004;Zhang et al 2005;Levy et al 2009;Newton-Cheh et al 2009a,b;Chen et al 2010;Tomaszewski et al 2010;Johnson et al 2011;Liu et al 2011;Fung et al 2012), we focused specifically below on the (+), (À), and (=) effects of mutant alleles on BP and urinary protein excretion (a commonly used index for renal damage).…”
Section: Strain Generation and Phenotyping Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Specific polymorphisms in the C -reactive protein gene predicted a higher risk for CKD progression, resistant to the action of ACE inhibitors in African-American patients (Hung et al, 2010). Finally, mutations in the human methylenetetrahydrofolate reductase (MTHFR) gene were associated with elevated levels of homocysteine and a faster decline of renal function over time in African-American patients (Fung et al, 2011). Very recently a study, conducted in a population of Hispanic descent reported an association between polymorphisms of vascular endothelial growth factor (VEGF) and hypertensive nephropathy with subsequent progression to ESRD (Yang et al, 2011).…”
Section: Epidemiology Of Hypertensive Nephrosclerosismentioning
confidence: 99%
“…Recently, SNPs have been used as a tool for predicting diseases (12) in addition to carcinogenesis (13,14). The MTHFR gene A1298C polymorphism has been implicated in several diseases (15,16), including various types of cancer (17,18), and has been investigated in relation to the risk of PC but with inconclusive results (19)(20)(21)(22)(23)(24)(25)(26)(27). Among the nine eligible casecontrol studies, three considered the MTHFR gene A1298C polymorphism as a genetic marker for PC (19,24,26), while six reported negative associations between the two (20)(21)(22)(23)25,27).…”
mentioning
confidence: 99%